Kajian Penggunaan Sistem Binaan Berindustri (IBS) Bagi Projek Pembinaan Pasca Covid-19 - Mohd Jailani, Nurul Syafiqah Izzatie; Kasim, Narimah; Mohd Noh, Hamidun; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2022)
Industrial building system (IBS) has been considered one of the effective ways to improve quality and efficiency in a construction project. However, many contractors are still comfortable with the use of conventional systems in construction projects where it requires a lot of manpower. Therefore, the use of IBS technology is the best during the Covid-19 pandemic because it does not require much labor and can avoid 3C i.e. crowded, confined, and close conversation. The aim of this study was to examine the IBS utilization strategy for construction projects during Covid-19. Therefore, the objectives of this study are to identify the existing challenges among contractors and the strategy of using IBS for the construction project during Covid-19. To achieve these objectives, this study uses quantitative methods through the distribution of questionnaires for data collection. Respondents for this study consisted of G7 contractors who have construction projects in Kuala Terengganu. Questionnaires were distributed and received 43 out of 145 which is 31% of the total. The data obtained were analyzed through SPSS software. The results show that the strict standard operation procedure (SOP) is a challenge that needs to be faced by contractors in handling IBS projects during Covid-19. In addition, improving IBS installation skills through training and education is a strategy of using IBS for construction projects during Covid-19. In conclusion, this study can benefit the construction industry in IBS technology and give awareness to contractors that the use and knowledge of technology especially IBS is very important during Covid-19.